Skin and bones: creative cities and the transformation of an urban garment district - Kotzen, Bronwyn (My University, 2011)
Set against rising levels of confidence within a new creative economy, creative industrial clusters are increasingly emphasizing their roles as significant drivers of local economic development. Fashion is recognised as one of these “creative industries”. As this multi-billion dollar global industry moves manufacturing operations from local sites to third world countries abroad, garment production has become a sum of disparate entities. This phenomenon is no different in the South African industry. Johannesburg’s Fashion District, located on the eastern edge of the downtown CBD, is a tangible reminder of a region once at the forefront of the South African fashion industry. It serves as a symbol of a city in transformation and a precinct rich in future creative and economic potential. Without a successful garment district, or industry centre the fashion industry faces a difficult future. Although the changing racial landscape of the Post- Apartheid inner city revealed the organic clustering of micro practitioners into the district, this economic incubator remains an unidentifiable home to an invisible industry hidden in the carcasses of its many neglected buildings. The injection of millions of Rands worth of public sector upgrades, has done little for the development of this ‘creative industrial cluster’. The successful transformation of this industrious urban garment district requires a radical rethinking of local context and production processes. The vertical integration of these parts could see the Fashion District become a clustered urban garment campus, a point of congregated resources synonymous with global and local centers of creative excellence, providing the tools for the regeneration and transfiguration of urban space consumption not only to its former glory as a once thriving garment district, but to its aspiration as an uniquely African precinct in an attempt to re-connect production and the city